ANALISIS FENOMENA FEAR OF MISSING OUT SELEBRITI PADA KONSER BLACKPINK JAKARTA DI TWITTER - Tannia, Fennita; Priscillia, Bernice; Scholus, Jessica Elisabeth (JURNAL SIGNAL, 2023)
Having a great musical influence, K-pop music is in demand by many international communities, including Indonesia. The large number of fans in Indonesia has made K-Pop industry players vying to hold K-Pop activities such as concerts. The Blackpink concert is one of the biggest concerts in Indonesia in 2023, offering and uplifting the fans. Not only that, the popularity of the Blackpink concert also caused FoMO, especially among celebrities. The FoMO phenomenon in celebrities themselves had angered Blackpink fans by expressing it on social media Twitter and making the issue a trending topic. From the magnitude of the FoMO phenomenon that occurs to these celebrities, this study is entitled "Fear of Missing Out Celebrity Phenomenalism Analysis at Blackpink Jakarta Concert on Twitter" to analyze how the FoMO phenomenon can occur and its impact on these celebrities. To obtain research results, researchers use the uses and gratification theory combined with qualitative descriptive methods to explain the phenomena that occur and draw conclusions. Data was taken by interviewing several sources with main criteria such as using Twitter and knowing the Blackpink Jakarta concert. Observations were also made on Twitter media through hashtags, mentions, and online interactions regarding the Blackpink concert in Jakarta. Thus, this research contributes to understanding the FoMO phenomenon in celebrities at the Blackpink Jakarta concert and how it influences motivation and impacts Twitter users. The study results show that BlackPink fans' use of Twitter and responses to negative news about celebrity Kiky Saputri reflect the need for information, social interaction, and emotional fulfilment in the context of FoMO at the BlackPink Jakarta concert. Drivers showed their dedication in defending the idol and reminiscing precious moments, while their perception and interest in BlackPink remained strong despite the different views of non-fans. Keywords: Fear of Missing Out, celebrity, k-pop fans, Twitter, Blackpink concert